A universal anti‐cancer vaccine: Chimeric invariant chain potentiates the inhibition of melanoma progression and the improvement of survival. Issue 4 (5th December 2018) - Sharbi‐Yunger, Adi; Grees, Mareike; Cafri, Gal; Bassan, David; Eichmüller, Stefan B.; Tzehoval, Esther; Utikal, Jochen; Umansky, Viktor; Eisenbach, Lea
Abstract : For many years, clinicians and scientists attempt to develop methods to stimulate the immune system to target malignant cells. Recent data suggest that effective cancer vaccination requires combination immunotherapies to overcome tumor immune evasion. Through presentation of both MHC‐I and II molecules, DCs‐based vaccine platforms are effective in generating detectable CD4 and CD8 T cell responses against tumor‐associated antigens. Several platforms include DC transfection with mRNA of the desired tumor antigen. These DCs are then delivered to the host and elicit an immune response against the antigen of interest. We have recently established an mRNA genetic platform which induced specific CD8 + cytotoxic T cell response by DC vaccination against melanoma. In our study, an MHC‐II mRNA DCs vaccine platform was developed to activate CD4 + T cells and to enhance the anti‐tumor response. The invariant chain (Ii) was modified and the semi‐peptide CLIP was replaced with an MHC‐II binding peptide sequences of melanoma antigens. These chimeric MHC‐II constructs are presented by DCs and induce proliferation of tumor specific CD4 + T cells. When administered in combination with the MHC‐I platform into tumor bearing mice, these constructs were able to inhibit tumor growth, and improve mouse survival. Deciphering the immunological mechanism of action, we observed an efficient CTLs killing in addition to higher levels of Th1 and Th2 subsets in the groups immunized with a combination of the MHC‐I and MHC‐II constructs. These universal constructs can be applied in multiple combinations and offer an attractive opportunity to improve cancer treatment. Abstract : What's new? The development of anti‐cancer vaccines is moving towards a multiple epitope approach, which potentiates both cytotoxic T cells (CTLs) and Helper T (Th) cells. Here, using a mouse melanoma model, the authors provide an mRNA vaccine platform that is highly efficient in eradicating the tumor. They utilize a chimeric invariant chain in combination with a chimeric β2m chain to activate both CTLs and Th cells, and to potentiate the inhibition of melanoma progression and improvement of survival. The system is modular and can be applied to multiple cancers.